2017
DOI: 10.1371/journal.pone.0178835
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an enantiopure bivalent nicotine vaccine using synthetic peptides

Abstract: Clinical outcomes of anti-nicotine vaccines may be improved through enhancements in serum antibody affinity and concentration. Two strategies were explored to improve vaccine efficacy in outbred mice: the use of enantiopure haptens and formulation of a bivalent vaccine. Vaccines incorporating natural (-) nicotine haptens improved relative antibody affinities >10-fold over (+) haptens, stimulated a two-fold boost in nicotine serum binding capacity, and following injection with 3 cigarette equivalents of nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Current parenteral and mucosal nicotine vaccines have been published with varying degrees of efficacy [13][14][15][16][17][18][30][31][32] and they all demonstrate significant levels of anti-nicotine antibodies that are able to block nicotine from entering the brain. Despite this similarity, the challenge and nicotine analysis methods vary and nicotine recovery tends to be low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current parenteral and mucosal nicotine vaccines have been published with varying degrees of efficacy [13][14][15][16][17][18][30][31][32] and they all demonstrate significant levels of anti-nicotine antibodies that are able to block nicotine from entering the brain. Despite this similarity, the challenge and nicotine analysis methods vary and nicotine recovery tends to be low.…”
Section: Discussionmentioning
confidence: 99%
“…While effective, recently there has been a shift away from using [ 3 H]-nicotine for nicotine challenges, and towards using nicotine tartrate to assess the distribution of nicotine by GC/MS, LC/MS or HPLC. However, unlike [ 3 H]-nicotine, that is typically if not always delivered intravenously (IV), non-tritiated forms of nicotine have been delivered subcutaneously (SC) [13][14][15][16], IV [17], or intraperitoneally (IP) [18], all of which resulted in low levels of recovery, regardless of the dose administered. This does not necessarily permit nicotine vaccines evaluated in vivo to be properly assessed due to the low recovery rates in the brain and the sera.…”
Section: Introductionmentioning
confidence: 99%
“…It would be indicated for the following groups of subjects: (a) heavy smokers who have made multiple unsuccessful attempts to quit using different methods; (b) patients who are highly motivated to quit; and (c) patients who have positive attitudes toward vaccines 20 . Modifications designed to improve serum antibody affinity are being tested and may improve the performance of future clinical candidate vaccines [21][22][23] .…”
Section: Vaccinesmentioning
confidence: 99%
“…9–12 We have used this carrier to produce a nicotine vaccine for smoking cessation and have shown that the Ab concentrations induced in mice and rats can bind supraphysiological doses of nicotine and prevent nicotine-induced toxicity. 8,13,14…”
Section: Introductionmentioning
confidence: 99%